Dietary protein requirement of lemon fin barb hybrid (Barbonymus gonionotus Bleeker 1849 ♀ × Hypsibarbus wetmorei Smith 1931 ♂) fingerlings - Rosle, Suharmili (2017)
Lemon fin barb hybrid (female Barbonymus gonionotus × male Hypsibarbus wetmorei) was first produced in 2004 with a novel intention as a poor man’s fish. At present, the fish is commercially raised with tilapia or catfish diets since no specific diet has been developed for the hybrid. As protein is the most important and costliest component in an aquafeed, the dietary protein requirements of lemon fin barb hybrid fingerlings were investigated in this study which included the optimal dietary protein and energy requirements, the effectiveness of defatted black soldier fly (Hermetia illucens) meal, poultry offal meal and soybean meal as fishmeal replacement and the apparent digestibility coefficients (ADC) of selected feedstuffs. Practical test diets were used in all feeding trials and the effects of these diets on the growth performance, proximate body composition, nutrient and amino acid retentions, and histopathological parameters of the fish were determined. In Experiment 1, five isocaloric (16 kJ g-1) diets containing varying protein levels ranging from 20 to 40% were tested. Six diets with three dietary protein levels (25, 30 and 35%) and two energy levels (16 and 17 kJ g-1) were evaluated in Experiment 2 while the performances of five isonitrogenous (30% protein) and isocaloric (17 kJ g-1) diets with varying dietary level of defatted black soldier fly pre-pupae (BSFP) meal (0, 25, 50, 75 and 100%) as fishmeal replacement were assessed in Experiment 3. In Experiment 4 and 5, similar experimental protocols as in Experiment 3 were adopted in which poultry offal meal (POM) and soybean meal were tested as fishmeal replacement, respectively. Best diets from Experiments 3, 4 and 5 were simultaneously evaluated in Experiment 6 while in Experiment 7, the apparent digestibility coefficient (ADC) of dry matter, nutrients and energy of fishmeal, defatted BSFP, defatted POM, defatted soybean meal, rice bran and corn meal, and their apparent availability coefficent (AAC) of amino acids in the hybrid fish were studied.